Nano-additives incorporated water in diesel emulsion fuel: Fuel properties, performance and emission characteristics assessment. (1st August 2018) - Hasannuddin, A.K.; Yahya, W.J.; Sarah, S.; Ithnin, A.M.; Syahrullail, S.; Sidik, N.A.C.; Abu Kassim, K.A.; Ahmad, Y.; Hirofumi, N.; Ahmad, M.A.; Sugeng, D.A.; Zuber, M.A.; et al.
Graphical abstract: Highlights: Nano-additives influenced the oxidative thermokinetics of the fuel. The CO emissions were reduced by using nano-additives. E10 showed the lowest mean and maximum diameter of PM particles. Abstract: The main objective of the study was to improve the fuel properties, performance and reduce the level of hydrocarbon (HC) and carbon monoxide (CO) when running with water in diesel emulsion fuel (W/D) by adding various nano-additives. Aluminium Oxide (Al2 O3 ), Copper(II) Oxide (CuO), Magnesium Oxide (MgO), Manganese(IV) Oxide (MnO) and Zinc Oxide (ZnO) nano-additives were selected for W/D with 10% water (E10). Each nano-additive was added to E10 at a dosage of 50 ppm and further denoted as nano-additive emulsion fuel: E10Al2 O3, E10CuO, E10MgO, E10MnO and E10ZnO. The properties (density, viscosity, water droplet size, stability period and oxidative thermokinetics), performance (torque, brake power, brake specific fuel consumption (BSFC), and emission (nitrogen oxides (NOx ), particulate matter (PM), carbon dioxide (CO2 ), CO and HC) of each test fuel were investigated. Overall, nano-additives tended to increase density, viscosity, water droplet size and oxidative thermokinetics but decrease the stability period. The nano-additives resulted in a marginal increase of performance with the E10Al2 O3 yielding the highest reduction in BSFC. The nano-additives also lowered the brake specific CO (BSCO) emissions compared to Euro 2 standard diesel (D2) by up to 17% with E10ZnO. Nano-additives produced from different metals impact the fuel properties, performance and emissions differently. Al2 O3 is nominated as the best nano-additive due to the smallest water droplet size, highest DTGmax and its consistency in increasing the torque and reducing the BSFC, brake specific NOx (BSNOx ), BSCO compared to other nano-additives. That is to say, nano-additives coupled with a W/D has the potential to reduce BSFC and BSCO simultaneously.